A qualitative study about how families coped with managing their well-being, children's physical activity and education during the COVID-19 school closures in England. - Lisa Woodland; Ava Hodson; Rebecca K Webster; Richard Amlôt; Louise E Smith; G James Rubin (PLoS ONE, 2022)
In 2020, schools in England closed for six months due to COVID-19, resulting in children being home-schooled. There is limited understanding about the impacts of this on children's mental and physical health and their education. Therefore, we explored how families coped with managing these issues during the school closures. We conducted 30 qualitative interviews with parents of children aged 18 years and under (who would usually be in school) between 16 and 21 April 2020. We identified three themes and eight sub-themes that impacted how families coped whilst schools were closed. We found that family dynamics, circumstances, and resources (Theme 1), changes in entertainment activities and physical movement (Theme 2) and worries about the COVID-19 pandemic (Theme 3) impacted how well families were able to cope. A key barrier to coping was struggles with home-schooling (e.g., lack of resources and support from the school). However, parents being more involved in their children's personal development and education were considered a benefit to home-schooling. Managing the lack of entertainment activities and in-person interactions, and additional health worries about loved ones catching COVID-19 were challenges for families. Parents reported adverse behaviour changes in their children, although overall, they reported they were coping well. However, pre-existing social and educational inequalities are at risk of exacerbation. Families with more resources (e.g., parental supervision, access to green space, technology to facilitate home-schooling and no special educational needs) were better able to cope when schools were closed. On balance, however, families appeared to be able to adapt to the schools being closed. We suggest that policy should focus on supporting families to mitigate the widening health and educational gap between families with more and less resources.